Effects of Education Based on Focus Group Discussions on Menstrual Health Behaviors of Female Adolescents in Boarding Centers of the Welfare Organization, Tehran, Iran - Shayesteh Shirzadi; Parinaz Doshmangir; Hassan Mahmoodi; Negin Niksadat; Mohammad Hossein Taghdisi; Davood Shojaeizadeh* (Hamadan University of Medical Sciences, 2015)
Background and Objectives: Problems caused by menstruation are common among women. Focus group discussions are a method of data collection in which a small group of participants discuss a specified topic or issue. This study mainly aimed to determine the effects of health education based on focus group discussions on the promotion of health behaviors of female adolescents residing boarding centers of the Welfare Organization (Tehran, Iran) during their menstruation periods. Materials and Methods: This quasi-experimental interventional study recruited all eligible 12-19-year-old female residents (n=61) of the boarding centers affiliated to the Welfare Organization, Tehran, Iran. The data collection tool was a questionnaire including demographic information and puberty health behaviors (health behaviors during the menstruation period). The questionnaires were completed through interviews before and one month after training. The educational intervention lasted for three months. Data were analyzed using paired t and Kolmogorov-Smirnov tests in SPSS16. Results: The mean scores of performance increased from 12.11±4.43 before the intervention to 16.50±2.79 after the intervention (P<0.001). Conclusion: Since the educational intervention based on focus group discussions had positive effects on the participants' puberty health, such discussions are recommended to educate adolescent girls about puberty issues.